(3GdJShjb YHQ GdCfJQfJ (B/s - (3GdYdGb, HTjQ YHGSs ((3YeGf(B: s (3GdhQGb ddfTQ hGdJhRjY(B, s, 2002)
(3eONd Gdi GdJShjb YHQ GdCfJQfJ(B- (3GdeaGgje GdCSGSjI ddJShjb YHQ GdCfJQfJ(B- (3GdJShb YHQ GdCfJQfJ (B- (3GdJShjb YHQ GdCfJQfJ ajeG Hjf efTBJ GdCYeGd(B- (3eSJbHd GdJShjb YHQ GdCfJQfJs
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3JcfhdhLjG GdeYdheGJs